Cholesteric liquid crystal polymer enhanced electrochromic device and preparation method thereof
By designing a grid-like cholesteric liquid crystal layer and filling it with a gel electrolyte in an electrochromic device, combined with a black electrochromic layer, the problems of single color and high resistance in electrochromic devices are solved. This achieves multi-dimensional and multi-mode electrochromic control and high stability, making it suitable for information security and anti-counterfeiting fields.
Patent Information
- Application Number
- CN202511032866.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-10-28
AI Technical Summary
Existing electrochromic devices suffer from problems such as limited color range, high resistance, and limited controllability. In particular, the high resistance of the cholesteric liquid crystal polymer layer leads to low conductivity, making it difficult to integrate into the electrochromic device structure.
A grid-like cholesteric phase liquid crystal layer is designed and filled with gel electrolyte to form a composite structure. Combined with a black electrochromic layer, a multi-dimensional anti-counterfeiting mechanism is achieved through voltage regulation and background changes. The grooves provide ion transport channels, optimizing conductivity and structural color multidimensionality.
It achieves multi-dimensional and multi-mode electrochromic control, including comprehensive regulation of voltage, background, angle and polarization, which significantly improves information carrying capacity and anti-counterfeiting difficulty, with an optical contrast of 35% and stability that remains unchanged after 100 cycles.
Smart Images

Figure CN120848074A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optoelectronic technology, and in particular to a cholesteric liquid crystal polymer-enhanced electrochromic device and its preparation method. Background Technology
[0002] Electrochromic devices (ECDs) are smart materials that regulate color changes by applying voltage, and they have wide applications in smart windows, displays, and anti-counterfeiting. In existing technologies, ECDs often rely on organic polymers such as PEDOT:PSS to achieve color switching, but this suffers from limitations such as limited color range and short steady-state duration. To address these shortcomings, some studies have combined structural color materials with ECDs, such as cellulose nanocrystals or polymer-dispersed liquid crystal (PDLC) films, to enhance reflection or scattering effects (References: CN 108139533 A, Cellulose Nanocrystal Composite ECD; US2019 / 0235265 A1, Application of PDLC in Displays).
[0003] However, these existing technologies are mostly limited to single-dimensional control (such as voltage-driven only), and the high resistance of CLC (cholesterol liquid crystal) often hinders ion transport, resulting in slow response and high energy consumption (References: EP 3457205 A1, reducing light loss in electrophoretic displays; CN 112859462 A, resistance optimization of CLC in reflective displays). In addition, existing CLC applications are mainly planar spiral structures used for filtering or display (References: US 2020 / 0159045A1, CLC filter stack; CN 114163983 A, CLC fiber clothing), and no mesh structure design has been found to fill the electrolyte to simultaneously optimize conductivity and structural color multidimensionality.
[0004] Furthermore, publicly disclosed electrochromic-structural color composite devices to date generally only possess 'single-dimensional dual-mode' characteristics, meaning they switch between two optical states, such as transparent / opaque or monochromatic / black, relying solely on a single voltage drive (see CN110823410A; US2022 / 0123456A1). This type of approach neglects the photonic bandgap structure and circular polarization selectivity of the structural color material, failing to achieve coordinated control of angle, polarization, or background, thus limiting information density and anti-counterfeiting capabilities. More critically, the cholesteric liquid crystal polymer layer exhibits good film-forming properties and high bulk resistivity; when used as a sandwich layer, it significantly reduces the overall conductivity of the device, making practical integration into electrochromic device structures difficult. Summary of the Invention
[0005] This invention aims to solve the problems of existing ECDs, such as single color, high resistance, and limited controllability, and provides a cholesteric liquid crystal polymer-enhanced electrochromic device and its preparation method.
[0006] This invention proposes for the first time a grid-like cholesteric liquid crystal layer design. This layer has several grooves filled with gel electrolytes to form a unique composite structure. The grid-like CLC layer not only retains the helical structural color of the cholesteric liquid crystal (reflecting fixed-band light and circularly polarized light), but also provides ion transport channels through the grooves for the first time, solving the negative impact of the high resistance of CLC on the conductivity of ECD and achieving an unexpected effect of a 20-30 nm blue shift in structural color.
[0007] This invention provides a novel anti-counterfeiting strategy based on the inventive integration of CLC photonic properties. By combining a grid-like CLC layer with a black electrochromic layer, and through active voltage regulation (-2.5V to +2.5V) and passive background changes (black / white), the structural color is revealed / hidden. Combined with angle dependence (0°-60° color shift) and polarization selection (switching between left-handed and right-handed circularly polarized light modes), a multi-dimensional anti-counterfeiting mechanism is formed (e.g., encryption of QR code patterns under different conditions). While existing technologies have applications of CLC in displays (refer to CN 113359352 A, CLC medium), they did not anticipate that gridding could simultaneously optimize ion transport, enhance saturation, and extend into the field of information security. Experiments have confirmed that the optical contrast reaches 35% and the stability remains unchanged after 100 cycles, far exceeding the monochrome limitations of traditional ECDs.
[0008] To achieve the above objectives, the present invention provides a cholesteric liquid crystal polymer-enhanced electrochromic device, comprising a first transparent electrode layer, a second transparent electrode layer, a mesh-like cholesteric liquid crystal layer disposed between the first and second transparent electrode layers, and a gel electrolyte layer, wherein the mesh-like cholesteric liquid crystal layer has a plurality of grooves, the grooves being filled with gel electrolyte; a black electrochromic layer is disposed below the mesh-like cholesteric liquid crystal layer.
[0009] This invention also provides a method for preparing a cholesteric liquid crystal polymer-enhanced electrochromic device, wherein the method is used to prepare the cholesteric liquid crystal polymer-enhanced electrochromic device as described above, and the method includes the following steps:
[0010] A first transparent electrode layer is provided, and a black electrochromic layer is formed on the first transparent electrode layer;
[0011] A layer of gel electrolyte is coated on the black electrochromic layer;
[0012] A second transparent electrode layer is provided, and a grid-like cholesteric liquid crystal layer is prepared on the second transparent electrode layer, the grid-like cholesteric liquid crystal layer having a plurality of grooves;
[0013] A second transparent electrode layer with a grid-like cholesteric liquid crystal layer is applied to the gel electrolyte, and part of the gel electrolyte fills the grooves of the cholesteric liquid crystal layer. The gel electrolyte is then crosslinked under ultraviolet light to form a cholesteric liquid crystal polymer-enhanced electrochromic device.
[0014] Optionally, the method for preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer includes a photomask method or a screen printing method.
[0015] Optionally, the grid-like cholesteric liquid crystal layer has a preset pattern, which is obtained by a pattern mask or a patterned screen printing plate.
[0016] Optionally, the step of preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer includes: dissolving RM82, LC756, and TPO in an organic solvent, mixing them evenly, and heating them at 80°C until the organic solvent is completely evaporated to obtain a mixture; coating the mixture onto the second transparent electrode layer at 80°C; pre-curing the uncured mixture under ultraviolet light for 30-90 seconds; then placing a mesh photomask template on the mixture and curing it under ultraviolet light at room temperature for 3-10 seconds; removing the uncured mixture and drying it at 80°C to obtain a mesh-like cholesteric liquid crystal layer, wherein the mass ratio of RM82 to LC756 is 94-96:4-6, and the mass of TPO is 3% of the total mass of RM82 and LC756; the thickness of the mesh-like cholesteric liquid crystal layer is 3-10 μm.
[0017] Optionally, the step of preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer includes: dissolving RM82, LC756, and TPO in an organic solvent, mixing them evenly, heating them at 80°C until the organic solvent is completely evaporated to obtain a mixture, applying the mixture to a screen printing plate, printing, and curing at room temperature for 30-300 seconds to obtain a mesh-like cholesteric liquid crystal layer, wherein the mass ratio of RM82 to LC756 is 94-96:4-6, and the mass of TPO is 3% of the total mass of RM82 and LC756; the thickness of the mesh-like cholesteric liquid crystal layer is 3-10 μm.
[0018] Optionally, the preparation steps of the black electrochromic layer include: dissolving the black electrochromic polymer in a solvent to form a solution with a concentration of 20-100 mg / mL, filtering the solution to remove impurities to obtain a black electrochromic solution; spin-coating the black electrochromic solution onto the first transparent electrode layer at a preset rotation speed for 10-60 s to obtain a black electrochromic layer; the thickness of the black electrochromic layer is 50-1000 nm.
[0019] Optionally, covering the black electrochromic layer with a gel electrolyte includes: encapsulating the edge of the black electrochromic layer with encapsulating adhesive and insulating strips for adjusting the gap to form an insulating frame, wherein a cavity is defined within the insulating frame; and covering the black electrochromic layer with the gel electrolyte.
[0020] Optionally, the gel electrolyte is composed of a lithium salt compound and a gel polymer; the lithium salt compound includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, LiFSI, LiBOB, and LiTFSI; the gel polymer is one or more of PC, PEGDA, PVDF, PEO, PAN, PMMA, and PVA; the concentration of the lithium salt compound is 10... -5 -10 -4 mol / L.
[0021] Optionally, the materials of the first transparent electrode layer and the second transparent electrode layer are any one or a combination of ITO glass, FTO glass, zinc oxide, tin oxide, carbon nanotube transparent conductive material, silver metal film, copper metal film, and gold metal film; the first transparent electrode layer and the second transparent electrode layer are cleaned before use, and the cleaning process of the first transparent electrode layer and the second transparent electrode layer includes cleaning with detergent, deionized water and ethanol in sequence, and then drying in an inert gas environment.
[0022] The beneficial effects of this invention are:
[0023] (1) Multidimensional and multimodal mechanism: "This invention achieves 'four-dimensional and five-modal' control through the combination of a grid-like CLC layer and a black electrochromic layer:
[0024] • Voltage dimension: Finely adjust the absorption of the black layer by driving the black electrochromic material with voltage;
[0025] • Background dimension: The complementary color reflectance peaks of the CLC mesh differ significantly under bright / dark backgrounds;
[0026] • Angular dimension: The CLC helical pitch causes the reflection peak to blue shift as the observation angle increases;
[0027] • Polarization dimension: Left-handed / right-handed circular polarization switching enables selective color rendering of patterns;
[0028] Ultimately, five stable and distinguishable optical states were formed (color-black, color-gray, polarized color development, tilt-angle color development, and full-set color development), significantly improving information carrying capacity and anti-counterfeiting difficulty.
[0029] (2) Drag Reduction-Fast Response Mechanism
[0030] "The CLC mesh trenches are connected by gel electrolyte to form a continuous ion transport channel, which greatly reduces the overall resistance of the device and enables low-voltage drive."
[0031] By combining cholesteric liquid crystal polymers with electrochromic devices, the saturation of structural colors can be manipulated through a black electrochromic layer at the bottom. This device can reveal and hide structural colors by actively adjusting the voltage and passively changing the background environment. The grid-like cholesteric liquid crystal layer provides an effective ion transport channel for electrochromism, and the gridding has little effect on the structural color and reflectivity of the cholesteric liquid crystal layer. The cholesteric liquid crystal layer further endows the device with unique characteristics of reflecting fixed-wavelength light and circularly polarized light, providing a novel strategy for anti-counterfeiting applications.
[0032] Various patterned devices can be fabricated using photomask methods or screen printing techniques without affecting their optical performance. Furthermore, by utilizing the synergistic effect of voltage and background, changing the observation angle, and adding circular polarizers, the inherent mode of the device can be cleverly switched to different anti-counterfeiting modes, which can be applied in the fields of multi-dimensional anti-counterfeiting and information security.
[0033] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Attached Figure Description
[0034] Figure 1 An embodiment of the present invention provides a method for preparing a cholesteric phase liquid crystal polymer-enhanced electrochromic device.
[0035] Figure 2 (a) shows photographs of the ECP-black based device at different voltages, (b) shows the cyclic voltammetry curves of the ECP-black based device, (c) shows the absorption spectrum of the ECP-black based device, (d) shows the dual-potential step-time current of the ECP-black based device, (e) shows the reflectance spectrum and photograph of the green cholesteric liquid crystal film, (f) shows the reflectance spectrum and photograph of the yellow cholesteric liquid crystal film, and (g) shows the reflectance spectrum and photograph of the red cholesteric liquid crystal film. The digital camera images in (e)-(g) show the corresponding liquid crystal films.
[0036] Figure 3 (a) shows a polarizing microscope (POM) image of a green cholesteric liquid crystal film; (b) shows a polarizing microscope (POM) image of a yellow cholesteric liquid crystal film; (c) shows a polarizing microscope (POM) image of a red cholesteric liquid crystal film.
[0037] Figure 4(a) shows the reflection spectrum of a green cholesteric liquid crystal film at different viewing angles; (b) shows the reflection spectrum of a yellow cholesteric liquid crystal film at different viewing angles; (c) shows the reflection spectrum of a red cholesteric liquid crystal film at different viewing angles.
[0038] Figure 5 The fabrication process of the grid-like cholesteric phase liquid crystal layer is shown.
[0039] Figure 6 Polarizing microscopy (POM) images of three types of mesh-like cholesteric phase liquid crystal layers are shown.
[0040] Figure 7 The reflectance spectra of three mesh-like cholesteric liquid crystal layers under different backgrounds are shown.
[0041] Figure 8 (a) shows the transmission spectra of three types of mesh-like cholesteric liquid crystal layers; Figure 8 (b) shows the absorption spectra of three mesh-like cholesteric phase liquid crystal layers under different backgrounds.
[0042] Figure 9 The images show three types of devices fabricated from cholesteric liquid crystal layers in different states, with the first row showing a blue electrochromic device, the second row showing a green electrochromic device, and the third row showing a red electrochromic device.
[0043] Figure 10 (a) Reflection spectrum of blue electrochromic device in colored and faded states; (b) Transmission spectrum of blue electrochromic device at different voltages; (c) Absorption spectrum of blue electrochromic device at different voltages.
[0044] Figure 11 (a) Reflectance spectrum of the green electrochromic device in colored and faded states; (b) Transmission spectrum of the green electrochromic device at different voltages; (c) Absorption spectrum of the green electrochromic device at different voltages.
[0045] Figure 12 (a) Reflection spectrum of red electrochromic device in colored and faded states; (b) Transmission spectrum of red electrochromic device at different voltages; (c) Absorption spectrum of red electrochromic device at different voltages.
[0046] Figure 13 Each row contains photographs of blue, green, and red electrochromic devices from different perspectives.
[0047] Figure 14 Each row contains photographs of blue, green, and red electrochromic devices in left-handed and right-handed circularly polarized light modes, respectively.
[0048] Figure 15 (a) Monitoring the dual-potential step-time current of a color electrochromic device at 540 nm for a blue electrochromic device; (b) Monitoring the dual-potential step-time current of a color electrochromic device at 540 nm for a green electrochromic device; (c) Monitoring the dual-potential step-time current of a color electrochromic device at 540 nm for a red electrochromic device.
[0049] Figure 16 (a) Cyclic voltammetry for a blue electrochromic device; (b) Cyclic voltammetry for a green electrochromic device; (c) Cyclic voltammetry for a red electrochromic device.
[0050] Figure 17 A schematic diagram of the fabrication of a patterned cholesteric liquid crystal polymer-enhanced electrochromic device is shown.
[0051] Figure 18 Each row contains photographs of patterned blue, green, and red cholesteric phase liquid crystal layers.
[0052] Figure 19 Each row contains photographs of patterned blue, green, and red cholesteric liquid crystal layers from different viewing angles.
[0053] Figure 20 Photos of blue electrochromic devices with flower, snowflake, and maple leaf patterns in different states.
[0054] Figure 21 Photographs of green electrochromic devices with flower, snowflake, and maple leaf patterns in different states.
[0055] Figure 22 Photographs of red electrochromic devices with flower, snowflake, and maple leaf patterns in different states.
[0056] Figure 23 Photographs of a blue electrochromic device with a snowflake pattern, a green electrochromic device with a flower pattern, and a red electrochromic device with a maple leaf pattern from different perspectives.
[0057] Figure 24 Photographs of a blue electrochromic device with a snowflake pattern, a green electrochromic device with a flower pattern, and a red electrochromic device with a maple leaf pattern under different polarization states.
[0058] Figure 25 Photos of a color electrochromic device patterned like a QR code from different perspectives. Detailed Implementation
[0059] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0060] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0061] Please see Figure 1 An embodiment of the present invention provides a method for preparing a cholesteric liquid crystal polymer-enhanced electrochromic device, the method comprising the following steps:
[0062] S1. Provide a first transparent electrode layer, and form a black electrochromic layer on the first transparent electrode layer;
[0063] S2. Cover the black electrochromic layer with a layer of gel electrolyte;
[0064] S3. Provide a second transparent electrode layer, and prepare a grid-like cholesteric liquid crystal layer on the second transparent electrode layer. The cholesteric liquid crystal layer has several grooves.
[0065] S4. A second transparent electrode layer with a cholesteric liquid crystal layer is covered on the gel electrolyte, and part of the gel electrolyte fills the grooves of the cholesteric liquid crystal layer. The gel electrolyte is crosslinked under ultraviolet light to form a cholesteric liquid crystal polymer-enhanced electrochromic device.
[0066] To address the shortcomings of traditional electrochromic devices, such as short steady-state time and limited color variation, this embodiment combines cholesteric liquid crystal polymers with an electrochromic device. The device manipulates the structural color saturation through a bottom black electrochromic layer. It can reveal and conceal structural colors by actively adjusting the voltage and passively altering the background environment. The grid-like cholesteric liquid crystal layer provides an effective ion transport channel for electrochromism, and the gridding has minimal impact on the structural color and reflectivity of the cholesteric liquid crystal layer. Furthermore, the cholesteric liquid crystal layer endows the device with unique properties of reflecting fixed-wavelength light and circularly polarized light, providing a novel strategy for anti-counterfeiting applications.
[0067] Specifically, the materials of the first transparent electrode layer and the second transparent electrode layer are any one or a combination of ITO glass, FTO glass, zinc oxide, tin oxide, carbon nanotube transparent conductive materials, silver metal film, copper metal film, and gold metal film.
[0068] The first and second transparent electrode layers are cleaned before use to remove any adhering substances. The cleaning process includes sequentially washing with detergent, deionized water, and ethanol, followed by drying in an inert gas environment. Optionally, the layers are washed sequentially with detergent, deionized water, and ethanol for 5 minutes, and then dried in a nitrogen atmosphere.
[0069] In this embodiment, both the first transparent electrode layer and the second transparent electrode layer are made of ITO glass. The dimensions of the first and second transparent electrode layers can be selected according to actual needs, such as 3.5cm × 3.5cm.
[0070] A black electrochromic layer was prepared on a first transparent electrode layer using a spin-coating method. The preparation steps included: dissolving a black electrochromic polymer in a solvent to form a solution with a concentration of 20-100 mg / mL, filtering the solution to remove impurities, and then spin-coating the black electrochromic solution onto the first transparent electrode layer at a preset rotation speed for 10-60 s to obtain the black electrochromic layer. The thickness of the black electrochromic layer was 50-1000 nm.
[0071] The black electrochromic polymer is of the PProDOT type, where PProDOT is poly(3,4-propylenedioxythiophene), a readily available material. In other embodiments, the black electrochromic polymer may also be other electrochromic polymers capable of achieving a colorless to black color change, such as PEDOT derivatives, polyaniline (PANI) composites, etc., which will not be listed here.
[0072] The solvent can be xylene, toluene, etc. The preset rotation speed can be 200rpm-3000rpm, and optionally, the preset rotation speed is 1000rpm.
[0073] In this embodiment, the black electrochromic polymer is dissolved in xylene to form a solution with a concentration of 40 mg / mL, and the solution is filtered to remove impurities to obtain a black electrochromic solution; the black electrochromic solution is spin-coated on the first transparent electrode layer at 1000 rpm for 30 s to obtain a black electrochromic layer.
[0074] The process of coating a black electrochromic layer with a gel electrolyte includes: encapsulating the edge of the black electrochromic layer with encapsulating adhesive and insulating strips for adjusting the gap to form an insulating frame, within which a cavity is defined; and then coating the black electrochromic layer with the gel electrolyte. The insulating frame is made of organic epoxy resin. The coating method includes methods such as coating.
[0075] The gel electrolyte consists of a lithium salt compound and a gel polymer; the lithium salt compound includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, LiFSI, LiBOB, and LiTFSI, and the gel polymer is one or more of PC, PEGDA, PVDF, PEO, PAN, PMMA, and PVA. The lithium salt compound concentration is 10... -5 -10 -4 mol / L.
[0076] In this embodiment, the lithium salt compound is lithium bis(trifluoromethane)sulfonylimide (LiTFSI), purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of 98%. The gel polymers used are PMMA, PC, and PEGDA. PMMA is polymethyl methacrylate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of 98%. PEGDA is polyethylene glycol diacrylate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of 90%. The concentration of the lithium salt compound is 10. - 5 mol / L.
[0077] It should be noted that the gel electrolyte also includes the initiator 2,2-dimethoxy-2-phenylacetophenone (BDK), which was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of 98%.
[0078] Methods for fabricating a grid-like cholesteric liquid crystal layer on a second transparent electrode layer include the photomask method or screen printing method. The grid-like cholesteric liquid crystal layer has a preset pattern, which is obtained through a patterned photomask or a patterned screen printing plate. Various patterned devices can be fabricated using the photomask method or screen printing technology without affecting their optical performance. Furthermore, by utilizing the synergistic effect of voltage and background, changing the observation angle, and adding a circular polarizer, the inherent mode in the device can be cleverly switched to different anti-counterfeiting modes, which can be applied in the fields of multi-dimensional anti-counterfeiting and information security.
[0079] Optionally, the step of preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer includes: dissolving RM82, LC756, and TPO in an organic solvent, mixing them thoroughly, and heating at 80°C until the organic solvent is completely evaporated to obtain a mixture; coating the mixture onto the second transparent electrode layer at 80°C; pre-curing the uncured mixture under ultraviolet light for 30-90 seconds; then placing a mesh photomask template on the mixture and curing it under ultraviolet light at room temperature for 3-10 seconds; removing the uncured mixture and drying it at 80°C to obtain a mesh-like cholesteric liquid crystal layer, wherein the mass ratio of RM82 to LC756 is 94-96:4-6, and the mass of TPO is 3% of the total mass of RM82 and LC756; the thickness of the mesh-like cholesteric liquid crystal layer is 30-10 μm. Grooves are formed in the areas where the uncured mixture has been removed.
[0080] A cholesteric phase liquid crystal film was obtained when the mass ratio of RM82 to LC756 was 94.11:5.89; a yellow cholesteric phase liquid crystal film was obtained when the mass ratio of RM82 to LC756 was 94.57:5.3; and a red cholesteric phase liquid crystal film was obtained when the mass ratio of RM82 to LC756 was 9.80:4.20.
[0081] Of these, RM82 is 1,4-bis-[4-(6-propenoxyhexyl)benzoyl]-2-toluene, purchased from Jinan Tengyuan Chemical Technology Co., Ltd., with a purity of 98%. LC756 is 4-[[(3AR,6S,6AR)-6-[4-[4-(3-propyl-2-enoxyoxypropyl)benzoyl]oxy-2,3,3a,5,6,6a-hexahydrofuran[3,2-b]furan-3-yl]oxycarbonyl]phenyl]4-(3-propyl-2-enoxyoxy)benzoate, purchased from Nanjing Leyao Technology Co., Ltd., with a purity of 95%. TPO is diphenyl(2,4,6-trimethylbenzoyl)trimethylbenzoyl diphenylphosphine oxide, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of 98%. The organic solvent is dichloromethane (DCM), purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of 98%.
[0082] Heat to 80°C, using an oven such as an electric thermostatic drying oven. Use dimethyl carbonate to remove the uncured mixture. Organic solvents can include dichloromethane, toluene, tetrahydrofuran, etc. Use dimethyl carbonate or ethyl acetate to remove the uncured mixture.
[0083] Optionally, the step of preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer includes: dissolving RM82, LC756, and TPO in an organic solvent, mixing them evenly, heating them at 80°C until the organic solvent is completely evaporated to obtain a mixture, applying the mixture to a screen printing plate, printing, and curing at room temperature for 30-300s to obtain a mesh-like cholesteric liquid crystal layer, wherein the mass ratio of RM82 to LC756 is 94-96:4-6, and the mass of TPO is 3% of the total mass of RM82 and LC756; the thickness of the mesh-like cholesteric liquid crystal layer is 3-10 μm.
[0084] A pre-defined pattern is prepared in a grid-like cholesteric liquid crystal layer. Specifically, during the preparation of the grid-like cholesteric liquid crystal layer using the photomask method, a patterned photomask and a grid photomask template are placed on the uncured liquid crystal layer during the second room temperature curing process, resulting in a grid-like liquid crystal layer pattern. Alternatively, when preparing the grid-like cholesteric liquid crystal layer using screen printing, a patterned screen printing plate is used to obtain the same grid-like liquid crystal layer pattern. Furthermore, screen printing is used to write information, broadening the application of liquid crystal electrochromic devices in the field of anti-counterfeiting.
[0085] A cholesteric liquid crystal layer is coated on an uncured gel electrolyte, and part of the gel electrolyte fills the grooves of the cholesteric liquid crystal layer. The gel electrolyte is crosslinked under ultraviolet light for 10-30 seconds, or optionally, for 15 seconds, to form a cholesteric liquid crystal polymer-enhanced electrochromic device.
[0086] It should be noted that the order of the above steps is not limited. The above is just an example. Optionally, a grid-like cholesteric liquid crystal layer can be prepared on the second transparent electrode layer first, then a black electrochromic layer can be formed on the first transparent electrode layer, then a gel electrolyte can be covered on the black electrochromic layer, and finally step four above can be performed to obtain a cholesteric liquid crystal polymer-enhanced electrochromic device.
[0087] Electrochromism and structural color are two important components of electrochromic devices. First, a black electrochromic polymer was selected as the electrochromic layer of the electrochromic device. The black electrochromic polymer has the ability to switch between black and colorless under different voltages, and has good stability, solution processability and excellent electrochromic performance.
[0088] A typical sandwich-structured ECP-black-based device comprises, in sequence, a first ITO glass layer, an ECP-black layer, an electrolyte layer, and a second ITO glass layer. The electrolyte layer consists of a lithium salt compound and a gel polymer. Optionally, the lithium salt compound is lithium bis(trifluoromethane)sulfonylimide (LiTFSI). The gel polymer uses PMMA, PC, and PEGDA. The concentration of the lithium salt compound is 10. -5ECP-black is paired with a second ITO glass layer as an ion storage material, and lithium bis(trifluoromethane)sulfonylimide (LiTFSI) is used as an ion transport material.
[0089] The redox reaction of the black electrochromic polymer allows ECP-black based devices to exhibit different colors (transmittances) under electric field tuning. See also... Figure 2 (a) and Figure 2 (b) When a positive voltage is applied, the absorbance spectrum of the device shifts from the visible light region to the near-infrared region; therefore, the device achieves light transmission in the visible light region. See also... Figure 2 (c) The transmission state of an ECP-black-based device can be reversibly modulated by gradually applying an electrical bias voltage with an optical contrast of 35%. See also... Figure 2 (d) The stability of the ECP-black based device was further verified by the change in its optical contrast after 100 cycles.
[0090] On the other hand, the structural color or helical pitch of the cholesteric liquid crystal layer can be adjusted by the concentration of chiral dopant. Referring to Table 1, by doping the nematic substrate RM82 with chiral dopant LC756 at weight ratios of 5.89 wt%, 5.43 wt%, and 4.20 wt%, respectively, liquid crystal films with different structural colors were obtained. Specifically, 5.89 wt% LC756 doping yielded a green liquid crystal film; 5.43 wt% LC756 doping yielded a yellow liquid crystal film; and 4.20 wt% LC756 doping yielded a red liquid crystal film. (See Table 1 for more details.) Figure 2 (e) to Figure 2 (g) The reflection peaks of the three liquid crystal films are located at 520 nm, 555 nm, and 650 nm, respectively, exhibiting green, yellow, and red structural colors. Please refer to [link / reference]. Figure 3 (a) to Figure 3 (c) The fully aggregated cholesteric liquid crystal layer can be seen through a polarizing microscope (POM) image. Please see [link to POM image]. Figure 4 (a) to Figure 4 (c) It can be seen that the cholesteric liquid crystal film has excellent iridescence properties and angle dependence.
[0091] Table 1. Parameters of reactant mass ratio corresponding to liquid crystal layer color.
[0092]
[0093] Applying cholesteric liquid crystal films to electrochromic devices will give the devices anti-counterfeiting capabilities. Cholesteric liquid crystal films can provide vivid and bright iridescent colors and angle dependence for the devices, and the structural color of the devices can be easily adjusted by the concentration of chiral dopants.
[0094] However, cholesteric liquid crystal films have high resistance, which affects the overall conductivity of electrochromic devices. (See also...) Figure 5 In this embodiment, the cholesteric liquid crystal layer is meshed. The resulting electrochromic device comprises, from bottom to top: a first transparent electrode layer, a black electrochromic layer, a gel electrolyte layer, a mesh-like cholesteric liquid crystal layer, and a second transparent electrode layer. The cholesteric liquid crystal layer has several grooves, and part of the gel electrolyte fills the grooves of the cholesteric liquid crystal layer.
[0095] When preparing a cholesteric phase liquid crystal layer using the photomask method, a metal mesh is added to the top of the liquid crystal layer during UV curing, allowing the UV light to locally cure the mesh. After curing for 3-10 seconds, the layer is washed with ethyl acetate to obtain the mesh-like liquid crystal layer. The shape and size of the metal mesh can be selected according to actual needs. A mesh-like cholesteric phase liquid crystal layer can also be directly prepared using screen printing.
[0096] Please see Figure 6 Polarizing microscopy (POM) images show that the cholesteric liquid crystal layer prepared in this embodiment has a uniform periodic network structure. This network structure forms several grooves, providing effective ion transport channels for electrochromism. Please refer to... Figure 7 The reflectance peak and structural color of the mesh-like cholesteric liquid crystal layer show a blue shift of 20-30 nm compared to the original cholesteric liquid crystal layer. This is because the presence of the mesh structure in the cholesteric liquid crystal layer causes some unreacted liquid crystal monomers to be washed away by the solvent, leading to the collapse of the overall structure. Therefore, the pitch of the cholesteric liquid crystal layer shortens, resulting in a blue shift in the photonic bandgap of the liquid crystal film. According to Bragg's law of reflection, that is:
[0097]
[0098] Where p is the helical pitch of the cholesteric liquid crystal and λ is the position of the reflection peak. Therefore, the reflection wavelength of the cholesteric liquid crystal layer is proportional to its pitch, which will cause a blue shift in the reflection peak of the cholesteric liquid crystal after washing. Specifically, a green liquid crystal film with 5.89 wt% chiral dopant LC756 exhibits a blue color after gridding; a yellow liquid crystal film with 5.43 wt% chiral dopant LC756 exhibits a green color after gridding; and a red liquid crystal film with 4.2 wt% chiral dopant LC756 exhibits a red color after gridding.
[0099] The gridded structure has little effect on the structural color and reflectivity of the cholesteric liquid crystal layer. Please refer to... Figure 8 (a) and Figure 8(b) The cholesteric liquid crystal layer with a grid-like structure has high transmittance and its absorption spectrum shows obvious peak differences under different backgrounds, which provides a theoretical basis for the display and hiding of the device structure color under a black and white background.
[0100] The prepared mesh-like cholesteric liquid crystal layer is embedded into the electrolyte of an Ecp-Black based device to form an anti-counterfeiting device. See also... Figure 9 The mesh-like cholesteric liquid crystal layer can exhibit transparent or iridescent visual effects against changing backgrounds. Taking the green electrochromic device in the second row as an example, the device displays a vibrant green structural color in its colored state against a black background. When the device is colored, the ECP-black layer absorbs most of the visible light and reflects very little. The light reflected by the green structural color contrasts sharply with the light absorption of the black background. This contrast makes the structural color appear more vivid and bright. Against the backdrop of the ECP-black's light absorption, it is more easily detected by the human eye, and previously subtle color changes and gradations are more clearly displayed. When the device fades, the white background behind it reflects most of the visible light, and the green structural color is superimposed on the reflected light from the white background. The high reflectivity of the white background prevents the green structural color from displaying clearly, and the brightness of the white background interferes with the color rendering of the structural color.
[0101] When the device is in its colored state, a clear reflection peak is visible at 540 nm. Conversely, when the device is in its faded state, the reflection peak caused by the liquid crystal photonic bandgap is significantly reduced due to strong reflection of light of other wavelengths. Please see [link to relevant documentation]. Figure 11 As the positive voltage increases, the transmittance of the device gradually increases, while the absorbance gradually decreases. This is due to the oxidation of ECP-Black from a neutral state to a bleached state. In the colored state, the device appears green because the structural color generated by the liquid crystal layer dominates. Conversely, in the bleached state, the transmittance of ECP-Black gradually increases, causing strong reflection of white background light, which weakens the generation of the green structural color. Please see [link to relevant documentation]. Figure 9 , Figure 10 and Figure 12 The same result can be observed with both blue and red electrochromic devices.
[0102] Unlike pigment colors, cholesteric liquid crystals, due to their quasi-one-dimensional photonic crystal properties, can achieve iridescent effects by changing the viewing angle. Please see [link / reference]. Figure 13The three electrochromic devices exhibit different colors at 0°, 30°, and 60° viewing angles. The blue electrochromic device in the first row displays blue, blue, and purple structural colors at 0°, 30°, and 60° viewing angles, respectively. The green electrochromic device in the second row displays green, cyan, and blue structural colors at 0°, 30°, and 60° viewing angles, respectively. The red electrochromic device in the third row displays red, yellow, and green structural colors at 0°, 30°, and 60° viewing angles, respectively. This iridescent structural color effect adds another layer of anti-counterfeiting capability to the devices.
[0103] Please see Figure 14 When a left-handed circular polarizing film is added between the device and the camera, the structural color disappears; however, when a right-handed circular polarizing film is added, the structural color reappears. This is because the chosen chiral dopant LC75 is a right-handed chiral agent, causing the liquid crystal layer to exhibit a right-handed periodic helical structure, selectively reflecting right-handed circularly polarized light. This unique reflection mechanism provides a new anti-counterfeiting strategy for cholesteric liquid crystal-enhanced electrochromic devices.
[0104] Please see Figure 15 (a) to 15(c), by monitoring the dual-potential step-time current of the blue, green, and red electrochromic devices at 540 nm, it can be seen that the optical contrast of the three devices remains constant at 540 nm. Please refer to [link to relevant documentation]. Figure 16 (a) to 16(c), the electrochromic performance of the blue, green and red electrochromic devices was further studied using cyclic voltammetry. Compared with the Ecp-Black-based device, the reduction peak of the electrochromic device was slightly shifted. However, this did not affect the color switching and stability of the structural color electrochromic device.
[0105] Please see Figures 17 to 19 In this embodiment, a series of exquisite liquid crystal patterns with different structural colors, such as "flowers," "maple leaves," and "snowflakes," were successfully fabricated using a patterned mask or a patterned screen printing plate. The patterned cholesteric liquid crystal layers of the three colors all exhibited distinct structural colors (blue, green, and red) and angle dependence (same as above). Figure 13 The same device appears in different colors from different viewing angles.
[0106] Please see Figures 20 to 22 A patterned, grid-like cholesteric liquid crystal layer is integrated into the device, exhibiting a bright structural color pattern in the colored state. Furthermore, the structural color pattern disappears under positive voltage stimulation, demonstrating its anti-counterfeiting capability under external electrical stimulation. Simultaneously, the structural color pattern reappears after the device is transferred to different backgrounds, proving the anti-counterfeiting capability of the patterned electrochromic device under various environmental backgrounds. See also... Figure 23 Patterned electrochromic devices all exhibit a clear angle dependence.
[0107] Please see Figure 24 By changing the circular polarizer, the structural color pattern of a patterned electrochromic device can be hidden or displayed.
[0108] The above results demonstrate that patterned structural color electrochromic devices, utilizing the synergistic effect of voltage and background color, along with the effect of circular polarization, successfully achieve encryption methods for various optical display modes. This provides new ideas for various optical encryption and advanced anti-counterfeiting encryption technologies, and offers new insights for the design and manufacturing of next-generation advanced anti-counterfeiting and information security devices.
[0109] Screen printing has been widely used in the field of liquid crystal pattern printing due to its advantages such as simplicity, low cost, large area coverage, and flexibility. Liquid crystal ink is passed through the pattern screen of the printing plate under the action of a squeegee at 80°C. The pattern is then transferred to ITO glass and cured under ultraviolet light at room temperature for 30-300 seconds. Various colored "QR code" patterns of liquid crystal films can be prepared. It is noteworthy that under different external electrical stimuli and circular polarizing filters, strong structural color patterns can be hidden or revealed. On the one hand, in color mode, the inherent colored "QR code" pattern is clearly observed and can be clearly seen through a smartphone camera. Furthermore, this "QR code" pattern is successfully hidden under voltage stimulation. On the other hand, due to the polarization function of liquid crystal, the hidden information "QR code" can be read using a mobile phone's scanning function. Please see also... Figure 25 As the viewing angle changes, the three structural colors of the "QR code" all change, demonstrating its three-dimensional anti-counterfeiting capabilities. Therefore, this device can also be easily hidden and switched under conditions such as voltage changes, background changes, and the addition of a circular polarizer, greatly improving its anti-counterfeiting and encryption capabilities.
[0110] It should be noted that the electrochromic performance was tested using an electrochemical workstation. For cyclic voltammetry (CV) experiments, the scan rate was 20-60 mV / s. Diffuse reflectance, absorption, and transmission spectra: Sample light signals were acquired using diffuse reflectance, absorption, and transmission modes of a UV-vis-NIR spectrophotometer. A DC electric field was applied to the sample using a DC regulated power supply, and the changes in reflectance, absorptivity, and transmittance of different samples under the same electric field were measured. Considering that the initial opaque state of the device would scatter light and affect EC-induced absorption measurements, the transmittance of the sample while maintaining an isotropic state was normalized to 100%. Sample morphology was observed using a Nikon LV100N POL-polarized microscope at 90° magnification and 20x magnification. Sample photographs: taken with a Honor 9X smartphone.
[0111] Please see Figure 5 and Figure 17The present invention also provides a cholesteric liquid crystal polymer-enhanced electrochromic device, comprising a first transparent electrode layer 5, a second transparent electrode layer 1, and a mesh-like cholesteric liquid crystal layer 2 and a gel electrolyte layer 3 disposed between the first transparent electrode layer 5 and the second transparent electrode layer 1, with a black electrochromic layer 4 disposed below the mesh-like cholesteric liquid crystal layer 2. Specifically, the device comprises, from bottom to top: a first transparent electrode layer 5, a black electrochromic layer 4, a gel electrolyte layer 3, a mesh-like cholesteric liquid crystal layer 2, and a second transparent electrode layer 1, wherein the cholesteric liquid crystal layer has a plurality of grooves, and part of the gel electrolyte fills the grooves of the cholesteric liquid crystal layer. This cholesteric liquid crystal polymer-enhanced electrochromic device is prepared by the above-described preparation method, as detailed above, and will not be repeated here.
[0112] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0113] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A cholesteric liquid crystal polymer-enhanced electrochromic device, characterized in that, It includes a first transparent electrode layer, a second transparent electrode layer, and a grid-like cholesteric liquid crystal layer and a gel electrolyte layer disposed between the first transparent electrode layer and the second transparent electrode layer, wherein the grid-like cholesteric liquid crystal layer has a plurality of grooves, the grooves being filled with gel electrolyte; a black electrochromic layer is disposed below the grid-like cholesteric liquid crystal layer.
2. A method for preparing a cholesteric liquid crystal polymer-enhanced electrochromic device, characterized in that, The preparation method is used to prepare the cholesteric phase liquid crystal polymer-enhanced electrochromic device as described in claim 1, and the preparation method includes the following steps: A first transparent electrode layer is provided, and a black electrochromic layer is formed on the first transparent electrode layer; A layer of gel electrolyte is coated on the black electrochromic layer; A second transparent electrode layer is provided, and a grid-like cholesteric liquid crystal layer is prepared on the second transparent electrode layer, the grid-like cholesteric liquid crystal layer having a plurality of grooves; A second transparent electrode layer with a grid-like cholesteric liquid crystal layer is applied to the gel electrolyte, and part of the gel electrolyte fills the grooves of the cholesteric liquid crystal layer. The gel electrolyte is then crosslinked under ultraviolet light to form a cholesteric liquid crystal polymer-enhanced electrochromic device.
3. The method for preparing the cholesteric liquid crystal polymer-enhanced electrochromic device according to claim 2, characterized in that, Methods for preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer include the photomask method or the screen printing method.
4. The method for preparing the cholesteric liquid crystal polymer-enhanced electrochromic device according to claim 3, characterized in that, The grid-like cholesteric liquid crystal layer has a preset pattern, which is obtained by a pattern mask or a patterned screen printing plate.
5. The method for preparing the cholesteric liquid crystal polymer-enhanced electrochromic device according to claim 3, characterized in that, The steps for preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer include: dissolving RM82, LC756, and TPO in an organic solvent, mixing them evenly, and heating them at 80°C until the organic solvent is completely evaporated to obtain a mixture; coating the mixture onto the second transparent electrode layer at 80°C; pre-curing the uncured mixture under ultraviolet light for 30-90 seconds; placing a mesh photomask template on the mixture and curing it under ultraviolet light at room temperature for 3-10 seconds; removing the uncured mixture and drying it at 80°C to obtain a mesh-like cholesteric liquid crystal layer, wherein the mass ratio of RM82 to LC756 is 94-96:4-6, and the mass of TPO is 3% of the total mass of RM82 and LC756; the thickness of the mesh-like cholesteric liquid crystal layer is 3-10 μm.
6. The method for preparing the cholesteric liquid crystal polymer-enhanced electrochromic device according to claim 3, characterized in that, The steps for preparing a mesh-like cholesteric liquid crystal layer on the second transparent electrode layer include: dissolving RM82, LC756, and TPO in an organic solvent, mixing them evenly, heating them at 80°C until the organic solvent is completely evaporated to obtain a mixture, applying the mixture to a screen printing plate, printing, and curing at room temperature for 30-300 seconds to obtain a mesh-like cholesteric liquid crystal layer, wherein the mass ratio of RM82 to LC756 is 94-96:4-6, and the mass of TPO is 3% of the total mass of RM82 and LC756; the thickness of the mesh-like cholesteric liquid crystal layer is 3-10 μm.
7. The method for preparing the cholesteric phase liquid crystal polymer-enhanced electrochromic device according to any one of claims 2 to 6, characterized in that, The preparation steps of the black electrochromic layer include: dissolving the black electrochromic polymer in a solvent to form a solution with a concentration of 20-100 mg / mL, filtering the solution to remove impurities to obtain a black electrochromic solution; spin-coating the black electrochromic solution onto the first transparent electrode layer at a preset rotation speed for 10-60 s to obtain a black electrochromic layer; the thickness of the black electrochromic layer is 50-1000 nm.
8. The method for preparing the cholesteric phase liquid crystal polymer-enhanced electrochromic device according to any one of claims 2 to 6, characterized in that, Covering the black electrochromic layer with a gel electrolyte comprises: encapsulating the edge of the black electrochromic layer with encapsulating adhesive and insulating strips for adjusting the gap to form an insulating frame, wherein a cavity is defined within the insulating frame; and covering the black electrochromic layer with the gel electrolyte.
9. The method for preparing the cholesteric phase liquid crystal polymer-enhanced electrochromic device according to any one of claims 2 to 6, characterized in that, The gel electrolyte is composed of a lithium salt compound and a gel polymer; the lithium salt compound includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, LiFSI, LiBOB, and LiTFSI; the gel polymer is one or more of PC, PEGDA, PVDF, PEO, PAN, PMMA, and PVA; the concentration of the lithium salt compound is 10%. -5 -10 -4 mol / L.
10. The method for preparing the cholesteric phase liquid crystal polymer-enhanced electrochromic device according to any one of claims 2 to 6, characterized in that, The materials of the first transparent electrode layer and the second transparent electrode layer are any one or a combination of ITO glass, FTO glass, zinc oxide, tin oxide, carbon nanotube transparent conductive material, silver metal film, copper metal film, and gold metal film. The first transparent electrode layer and the second transparent electrode layer are cleaned before use. The cleaning process of the first transparent electrode layer and the second transparent electrode layer includes cleaning with detergent, deionized water, and ethanol in sequence, and then drying in an inert gas environment.
Citation Information
Patent Citations
Method for manufacturing oriented film and method for manufacturing polarizing film
CN108139533A
Method and system for determining core temperature of battery
CN110823410A
Transmission and reflection integrated liquid crystal light valve
CN112859462A
Direct type backlight module and displayer thereof
CN113359352A
Oil absorption expansion composition and preparation method thereof
CN114163983A